2012
DOI: 10.1007/s10681-012-0626-z
|View full text |Cite
|
Sign up to set email alerts
|

Doubled haploids in tropical maize: II. Quantitative genetic parameters for testcross performance

Abstract: Single crosses (SC) of elite inbreds and open-pollinated populations (OP) are suitable source germplasm for doubled haploid (DH) line development in hybrid maize breeding, given that they combine a high population mean (x) for testcross performance with adequate response to selection (DG). This is the first study reporting testcross grain yield (TCGY) and dry matter content (TCDMC) evaluations of 131 DH lines developed from ten tropical source germplasm comprising five OP (OP1-OP5) and five SC (SC1-SC5). Gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Although improved seed set, reduced number of barren stalks, reduced anthesis-silking interval and lower incidence of common smut might suggest some positive purging of detrimental alleles [34], [35], the absence of grain yield improvement in the synthetic populations was disappointing and contrary to expectations [25], [27]. It must be noted, however, that seeds of the synthetic populations were produced on less vigorous homozygous lines while the seeds of the landraces were produced on vigorous heterozygous plants.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Although improved seed set, reduced number of barren stalks, reduced anthesis-silking interval and lower incidence of common smut might suggest some positive purging of detrimental alleles [34], [35], the absence of grain yield improvement in the synthetic populations was disappointing and contrary to expectations [25], [27]. It must be noted, however, that seeds of the synthetic populations were produced on less vigorous homozygous lines while the seeds of the landraces were produced on vigorous heterozygous plants.…”
Section: Discussionmentioning
confidence: 76%
“…Unlocking the genetic diversity present in the huge collections of maize landraces accessions by developing homozygous lines from these highly heterogeneous populations [18], [27] is of great interest for breeding. Both the single seed descent (SSD) and the in vivo double haploid (DH) techniques would be appropriate methods to produce fixed lines and purge the genetic load present in landraces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with the results of Wilde et al (2010), who reported that testcrosses of flint landraces and double haploid (DH) lines extracted from them without selection yielded 22 to 26% less than the commercial check hybrids. For tropical germplasms, Prigge et al (2012) found only a 17% lower GY for testcrosses of DH lines extracted from open‐pollinated varieties compared with the check hybrids. In our study, testcrosses of the best landrace, Viey, yielded only 17% less than the commercial checks.…”
Section: Discussionmentioning
confidence: 93%